Optimization of Solid Soap Containing Bentonite and Combination of Palm Oil and Virgin Coconut Oil for Cleansing Najs Mughalladzah - Ika Nustiana Anggraeni; Astri Desmayanti; Mufrod; Abdul Rohman (Journal of Food and Pharmaceutical Sciences, 2019)
This research was intended to formulate solid bentonite soap using combination of palm oil andvirgin coconut oil used for cleansing najs mughalladzah (extreme najs). Five formula of soap designated with AEapplying bentonite and combination of VCO and PO with different concentrations. The assessment of soapquality was based on soap hardness, foam stability, water content, total fatty acid, free fatty acid and free alkali.Evaluation results were analyzed using simplex lattice design (SLD) to obtain optimum formula. Verification ofoptimum formula was analyzed using one sample t-test with level of significance of 0.05. The results showedthat optimum concentration of bentonite was 4.06% with percentages of VCO 89.6% and PO of 10.4%. Based onone sample t-test, there is no significant difference (pH > 0.05) from foam stability and total fatty acid betweenthe predicted optimum formula as analyzed using SLD and verified result.